Knowledge Breakthroughs through Time in Mind and Action—An Outline of a New-Old Knowledge History - Arne Jarrick (Knowledge, 2023)
An outline of a research program on knowledge progress and strategies for knowledge breakthroughs through time, in two parts: A. An outline of five steps/stages in such processes and studies via a set of cases: 1. the inception of a new finding/discovery; 2. cognitive resistance to the new finding; 3. cognitive acceptance of the new finding but continuing resistance to its practical implementation or behavioural adjustment to it; 4. practical as well as cognitive acceptance; 5. openness (or not) to related further findings. B. Defense of my approach in view of criticism from representatives of new lines of research in what has been called knowledge history.